Sporadic Creutzfeldt–Jakob Disease Appears to Be Sporadic Fatal Insomnia: A Case Report and Review of the Literature - Sun Q (Dove Medical Press, 2021)
Qingqing Sun, Pingping Shen, Jiayi Tang, Hongmei Meng, Jiachun Feng, Zan Wang, Li Cui Department of Neurology and Neuroscience Center, The First Hospital of Jilin University, Changchun, People’s Republic of ChinaCorrespondence: Zan Wang; Li Cui Email wangzan@jlu.edu.cn; wangzanprof@163.com; lcui@jlu.edu.cnAbstract: Creutzfeldt–Jakob disease (CJD) subtypes are difficult to identify due to the heterogeneity of the clinical phenotype, and early accurate identification of sporadic CJD (sCJD) subtypes aids prognosis prediction. Currently, the diagnosis of sCJD subtypes is mainly based on brain tissue biopsy or autopsy. In this report, we present a case of confirmed sCJD initially presenting as insomnia. We described detailed information including clinical, electroencephalographic, polysomnographic, positron emission tomography-computed tomographic and other neuroimaging findings, cerebrospinal fluid biomarkers, skin tissue biopsy and whole blood PRNP gene sequencing in this patient. An extensive literature search was performed in order to better understand the diagnosis of various sCJD subtypes, particularly the thalamic form, sCJDMM2 (also known as sporadic fatal insomnia). Our study highlights sporadic fatal insomnia as a differential diagnosis of sCJD.Keywords: sporadic Creutzfeldt–Jakob disease, sporadic fatal insomnia, sCJDMM, polysomnography, PET